Evidence of the fine-structure constant in H0-tension - Maurice H.P.M. van Putten (Elsevier, 2021)
Modern precision measurements on Hubble expansion H(z) introduce two integral constraints on background models derived from early and late-time cosmology, based on Planck observations of the BAO and, respectively, H0, here normalized to ΛCDM. For H(z) coupled to Λ=(1−q)H2 of zero wave-number modes of cosmological spacetime with deceleration parameter q(z), we infer a coupling constant g<1 for H0 in tension with ΛCDM. Results from the Local Distance Ladder give g≃1−ξα with ξ=0.49±0.10. This result appears natural upon identifying H0-tension with breaking of T-duality in the Friedmann scale factor a(t) to the same order.